One Pot Synthesis of Multi-functional Tin Oxide Nanostructures for High Efficiency Dye-sensitized Solar Cells - Qamar, Wali; Azhar, Fakharuddin; Yasin, Amina; Mohd Hasbi, Ab. Rahim; Jamil, Ismail; Rajan, Jose (Elsevier Ltd, 2015)
Photoanode plays a key role in dye sensitized solar cells (DSSCs) as a scaffold for dye molecules, transport medium for photogenerated electrons, and scatters light for improved absorption. Herein, tin oxide nanostructures unifying the above three characteristics were optimized by a hydrothermal process and used as photoanode in DSSCs. The optimized morphology is a combination of hollow porous nanoparticles of size ∼50 nm and micron sized spheres with BET surface area (up to 29 m2/g) to allow large dye-loading and light scattering as well as high crystallinity to support efficient charge transport. The optimized morphology gave the highest photovoltaic conversion efficiency (∼7.5%), so far achieved in DSSCs with high open circuit voltage (∼700 mV) and short circuit current density (∼21 mA/cm2) employing conventional N3 dye and iodide/triiodide electrolyte. The best performing device achieved an incident photon to current conversion efficiency of ∼90%. The performance of the optimized tin oxide nanostructures was comparable to that of conventional titanium based DSSCs fabricated at similar conditions.